2018
DOI: 10.1002/pi.5691
|View full text |Cite
|
Sign up to set email alerts
|

Poly(polyhedral)s: synthesis and study of a new class of polyurethanes composed of homocubanes

Abstract: A new class of polyurethanes composed of homocubane‐based monomers has been synthesized and studied. Combining a basketane diol or a snoutane diol with various diisocyanates afforded the corresponding polymers in excellent yields and in high molecular weight (number‐average molecular weight (Mn) up to 49 kDa). The polyurethanes were found to be soluble in common organic solvents and displayed glass transition temperatures that ranged from 51 to 184 °C, depending on the structures of the monomers. © 2018 Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…We tried isomerization of various 1,4‐substituted cubanes into cuneanes (Table 1, entry 1–10). We employed the reaction conditions using silver nitrate as reagent or catalyst in MeOH/H 2 O solvent [13] . Symmetrically substituted 1,4‐substituted cubanes (R=R′, entries 1–3) were isomerized efficiently and gave corresponding cuneanes with varying regioisomer ratios.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tried isomerization of various 1,4‐substituted cubanes into cuneanes (Table 1, entry 1–10). We employed the reaction conditions using silver nitrate as reagent or catalyst in MeOH/H 2 O solvent [13] . Symmetrically substituted 1,4‐substituted cubanes (R=R′, entries 1–3) were isomerized efficiently and gave corresponding cuneanes with varying regioisomer ratios.…”
Section: Methodsmentioning
confidence: 99%
“…We employed the reaction conditions using silver nitrate as reagent or catalyst in MeOH/H 2 O solvent. [13] Symmetrically substituted 1,4-substituted cubanes (R=R', entries 1-3) were isomerized efficiently and gave corresponding cuneanes with varying regioisomer ratios. Isomerization of cubane 1 a and 1 b has already been conducted by Eaton [1] under slightly different conditions, and they reported almost the same ratio of 1,3-substituted cuneanes 2 and 2,6substituted cuneanes 4.…”
mentioning
confidence: 99%
“…They are soluble in polar organic solvents, decompose at relatively high temperature, and the Tg is higher than those of commercial PUs. It is expected that these new polymers will find application in products that need thermally robust PUs [67]. One pot technique for the production of GO/(hyper branched PU)(HPU) has been presented.…”
Section: Academic Journal Of Polymer Sciencementioning
confidence: 99%
“…The effects TPU with various amounts of boron nitride has on DC and AC conductivities and the free volume have been investigated [96]. Results of dielectric/electrical studies of onion-like carbon/PU composite films in very broad frequency and temperature are presented in a study [97]. By studying the spinning technique and the fiber topology, it was found that the characteristics of the PU solutions influence the spinning process and is able to affect the fiber topology [98].…”
Section: Other Contributionsmentioning
confidence: 99%